Falling racial inequality and rising educational inequality in US prison admissions for drug, violent, and property crimes - Christopher Muller; Alexander F. Roehrkasse (Proceedings of the National Academy of Sciences, 2025)
Using administrative and survey data, we show that there has been a sea change in the contours of American imprisonment. At the end of the twentieth century, inequality in the prison admission rates of Black and White Americans was comparable to inequality in the prison admission rates of people with and without a college education. However, educational inequality is now much greater than racial inequality in prison admissions for all major crime types. Violent offenses have replaced drug offenses as the primary driver of Black prison admissions and Black–White inequality in the prison admission rate. The prison admission rate of Black Americans has fallen, but the prison admission rate of White Americans with no college education has dramatically increased for all offense categories. These findings, which are robust to adjustments for changing selection into college attendance, contribute to a growing body of evidence documenting narrowing racial inequality and widening educational inequality in Americans’ life chances.